Shell length at sexual maturity and spawning cycle of Mytella guyanensis (Bivalvia: Mytilidae) from Costa Rica - Cruz, Rafael A; Villalobos, Carlos R (Revista de Biología Tropical, 1993)
A population of Mytella guyanensis from Costa Rica was studied for 12 months in order to determine shell length at sexual maturity, frecuency and duration of the spawning cycle under natural conditions. The smallest mature individual was 18 mm long. The mussels spawned from September through November and from February through April. Sexes were distinguishable in all individuals with a shell length greater than 30 mm. No evidence of protandry or hermaphroditism was observed. Sex ratios of M. guyanensis did not differ significantly of 1: 1.